1986
DOI: 10.1111/j.1095-8649.1986.tb04961.x
|View full text |Cite
|
Sign up to set email alerts
|

Upstream migration of adult Atlantic salmon, Salmo salar L., in the River Vefsna, northern Norway

Abstract: Daily ascents of adult Atlantic salmon (Salmo salar) in the Laksforsen waterfall in the River Vefsna were recorded over 3 years. Ascent was correlated to 12 physical and meteorological parameters by multiple regression analysis. Change in water temperature was included in the regression model in all 3 years, and change in river flow was also included in 2 of the 3 years. No other variable was included in the regression model at the 0.05 significance level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
3
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 5 publications
2
61
3
1
Order By: Relevance
“…The travel speeds of rainbow trout in this study are comparable with those reported for brown trout (Salmo trutta) (Rustadbakken et al 2004) but very slow in comparison with those reported for Atlantic salmon (Salmo salar) (Jensen et al 1986). Rainbow trout are known to migrate considerable distances (Meka et al 2003), and so fatigue is unlikely to explain the slow travel speed.…”
Section: Speed Of Travelsupporting
confidence: 73%
“…The travel speeds of rainbow trout in this study are comparable with those reported for brown trout (Salmo trutta) (Rustadbakken et al 2004) but very slow in comparison with those reported for Atlantic salmon (Salmo salar) (Jensen et al 1986). Rainbow trout are known to migrate considerable distances (Meka et al 2003), and so fatigue is unlikely to explain the slow travel speed.…”
Section: Speed Of Travelsupporting
confidence: 73%
“…The travel speed of migrating rainbow trout in this study was in the lower range of those reported for salmonids (Jensen et al 1986). Fast rates of upstream travel have been reported for salmonids through estuaries and the lower reaches of long rivers (Hawkins & Smith 1986;Heggberget et al 1988;Glova & Washbourne 1990) and during the first 10 days after entering the river (Heggberget et al 1996).…”
Section: Speed Of Travelcontrasting
confidence: 67%
“…Trépa-nier et al (1996) showed only limited effects of temperature on salmon upstream migration. Still, Jensen et al (1986) observed that Atlantic salmon passages upstream of rapids in a Norwegian river were correlated to increasing water temperature.…”
Section: Discussionmentioning
confidence: 99%